El Cuidar-Cuidado en el Paciente con Tuberculosis desde la Perspectiva de la Enfermera. Hospital Regional Docente de Trujillo - Alcántara Medina, Carla Lisbeth (2016)
This descriptive qualitative study seeks to describe, analyze and discuss “caring - care patients with tuberculosis from the perspective of nurse”. The theoretical bases are grounded in the theoretical concepts of care - care as Waldow (2008) y Boff (1999). They are involving nine staff nurses working in Medicine “A” of Regional Hospital Teaching of Trujillo. The semi -structured interview was used. Two categories emerged: the impact of care and caring process. The results show that the nurse for caring-care provided to patients with tuberculosis resonance and dissonance shown through the kindness and compassion was presented, but can also take an attitude of indifference to the patient, lack of time and absence of the familiar. Also during this care-care aesthetic and ethical dimension of care through communication with the patient and concern for the patient with responsibility and caring presence for presents and also in most cases providing patient education.